2017
DOI: 10.1039/c6nj03960j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of dimethyl malonate to 1,3-propanediol catalyzed by a Cu/SiO2catalyst: the reaction network and the effect of Cu+/Cu0on selectivity

Abstract: 1,3-Propanediol was synthesized via the hydrogenation of dimethyl malonate over a Cu/SiO2 catalyst. The reaction network and active sites were revealed for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The Cu 0 and Cu + species on the catalyst surface play different roles in catalytic reactions, such as activation of H 2 or adsorption of substrate. There are two steps of reaction in HMF hydrogenolysis to DMF, namely the hydrogenation of the side -CH = O groups and the following hydrogenolysis of -CH 2 -OH groups, which both need the activation of H 2 and adsorption of HMF ( Zheng et al, 2017 ). Therefore, XPS and XAES analyses were performed to evaluate the chemical state of Cu species on SiO 2 surface.…”
Section: Resultsmentioning
confidence: 99%
“…The Cu 0 and Cu + species on the catalyst surface play different roles in catalytic reactions, such as activation of H 2 or adsorption of substrate. There are two steps of reaction in HMF hydrogenolysis to DMF, namely the hydrogenation of the side -CH = O groups and the following hydrogenolysis of -CH 2 -OH groups, which both need the activation of H 2 and adsorption of HMF ( Zheng et al, 2017 ). Therefore, XPS and XAES analyses were performed to evaluate the chemical state of Cu species on SiO 2 surface.…”
Section: Resultsmentioning
confidence: 99%
“…Lomate et al also reported that Cu supported SiO 2 appears to be a complex function of acidity, which is the nature of copper species in the Cu/SiO 2 catalysts for LA hydrogenolysis. Zheng et al and Zhu et al performed hydrogenolysis reaction catalyzed by a copper‐supported material, correlation of surface‐active Cu species, and particle size versus activity. As demonstrated by Schittkowski et al, their bifunctional nature of Cu/ZrO 2 catalyst is applied in the hydrogenation of ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%
“…One centered at 917.5 eV that is ascribed to Cu 0 , and a second one at lower kinetic energy that ascribed to Cu + . [26,[48][49][50] It points out that even for low Cu content, some of the copper is reduced. However, for the samples having high Cu content only one peak centered at 917.5 eV is detected.…”
Section: Characterization Of the First Generation Of Catalystsmentioning
confidence: 99%